An examination of the local planning and investment programming processes in public works within the context of Mandanas-Garcia ruling the case of Pampanga and Biliran Provinces, Philippines - Cabral, Maria Catalina E.
This research examined the local planning and investment programming processes in public works within the context of the Supreme Court Ruling on the Mandanas-Garcia Cases (Mandanas-Garcia Ruling) and the consequent issuance of the Executive Order (EO) 138, series of 2021, focusing on the cases of Pampanga and Biliran provinces. It explored how LGUs are adapting to the new fiscal landscape and the expanded responsibilities of public infrastructure development. The study has profound implications for infrastructure planning, decentralization, and public works implementation across the Philippines. The study used a combined theoretical lens of decentralization theory (encompassing political, administrative, and fiscal dimensions) and collaborative governance theory (emphasizing inter-agency and multi-stakeholder engagement), along with urban and regional planning theory and gravity model perspectives. Focusing on the provinces of Pampanga and Biliran as case studies, the research indicated that the Mandanas-Garcia devolution reforms-by substantially increasing local governments' National Tax Allotments (NTA) and mandating the transfer of certain national functions to local government units (LGUs) have yielded mixed outcomes. The findings revealed practical implications for LGUs that despite increased fiscal resources, many still face technical and financial capacity gaps, resulting in continued reliance on national government agencies (NGAs) for project implementation and only minimal adjustments to local planning and budgeting processes. The study proposed a Transition Framework on Public Works for the Planning and Investment Programming Processes Post-Mandanas-Garcia Ruling. This framework underscores the value of collaborative governance, focusing on three key dimensions-political (inter-agency collaboration), administrative (LGUs' planning capacity), and fiscal/financial (efficient fund utilization). It highlights how integration and complementation of administrative, financial, and political resources across NGAS, LGUs. and the private sector can enable more effective and efficient planning, budgeting, and implementation of public works projects towards more sustainable urbanization and rural development. It provides a pathway towards close coordination with the Department of Public Works and Highways (DPWH) as the largest infrastructure agency of government, together with regular engagement with agencies such as the Department of Transportation (DOTr), the Department of Information and Communications Technology (DICT), the National Economic Development Authority (NEDA), and the Department of Interior and Local Government (DILG) in relation to workforce development and technical assistance on the strategic use of augmented fiscal resources. Capacity-building programs on financial management, budgeting, and alternative financing mechanisms (e.g. public-private partnerships) are also recommended, along with leveraging the PPP Code and Real Property Valuation and Assessment Reform Act (RPVARA) to unlock new funding and technical expertise. By adopting this multi-agency and multi-stakeholder collaborative approach. LGUs can optimize the devolution of public works functions under the Mandanas-Garcia Ruling and EO 138. Future research should further assess PPP Code applications, refine inter-LGU project planning guidelines, and evaluate RPVARA's implications for public works. This is to enhance fiscal autonomy and ensure that public investments translate into broader socio-economic benefits across Philippine regions.